2020
DOI: 10.3390/languages5020027
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Postalveolar English Obstruents by Spanish Speakers Learning English as a Foreign Language in Mexico

Abstract: The present study deals with the perception (identification and discrimination) of an English phonemic contrast (/t∫/–/∫/, as in cheat and sheet) by speakers of two Mexican varieties of Spanish who are learning English as a foreign language. Unlike English, Spanish does not contrast /t∫/ and /∫/ phonemically. Most Spanish varieties have [t∫], but not [∫]. In northwestern Mexico, [∫] and [t∫] find themselves in a situation of “free” variation—perhaps conditioned, to some extent, by social factors, but not in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…More specifically, consistent with one L1‐Spanish L2‐English study that reported a one‐allophone L1 variety advantage over the two‐allophone L1 variety with free allophonic variation in a scenario of L1–L2 allophonic split (López Velarde & Simonet, 2020), Chinese L1 speakers in our study who preferred to consistently use [w] rather than both allophones also enjoyed a clear advantage in correctly perceiving and lexicalizing the L2 /v/–/w/ contrast. Indeed, having one L1 phonemic category with a lot of variation makes it harder to separate that space into two separate L2 categories.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…More specifically, consistent with one L1‐Spanish L2‐English study that reported a one‐allophone L1 variety advantage over the two‐allophone L1 variety with free allophonic variation in a scenario of L1–L2 allophonic split (López Velarde & Simonet, 2020), Chinese L1 speakers in our study who preferred to consistently use [w] rather than both allophones also enjoyed a clear advantage in correctly perceiving and lexicalizing the L2 /v/–/w/ contrast. Indeed, having one L1 phonemic category with a lot of variation makes it harder to separate that space into two separate L2 categories.…”
Section: Discussionsupporting
confidence: 84%
“…Whereas previous findings support the role played by the L1 phonological category that is phonetically similar to its L2 counterpart in establishing a L2 dominant category, not much has been done on a learning scenario with a particularly high degree of difficulty, that involving an allophonic split, where the learners’ L1 has both phones but lacks the phonological contrast, that is, separate phonemes in the L2 are allophones of the same phoneme in the L1 (Eckman et al., 2003; López Velarde & Simonet, 2020). Moreover, little is known about whether L1 phonotactic rules can constrain the learning patterns for problematic L2 contrasts (see, however, Weber & Cutler, 2006, a study demonstrating the role of L1 phonotactics in the segmenting of continuous speech in the L2); this study aims to explore this novel issue under the allophonic split learning scenario in order to investigate the role of L1 phonology, allophony, phonotactics, and memory consolidation in the phonolexical encoding of novel words with problematic L2 contrasts.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations